2022
DOI: 10.54259/eajmr.v1i1.446
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Analysis of Chicken Rocket Mapping at Fast Food Restaurant Manarap Branch Banjarmasin

Abstract: Along with the changing times, the tendency of people to eat outside the home is increasing for various practical, economic and prestige reasons. Rocket Chicken is one of the fast food restaurant companies that has recently grown and has opened branch outlets everywhere, especially in the city of Banjarmasin. The role of price in buyer's perception is on product quality, value sacrifice and desire to buy, while location or place often determines the company's success, because location is closely related to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…This finding shows that, to achieve loyalty in the fast-food customer, it is necessary that the restaurants meet the expectations of satisfaction through the delivery of quality products and services, as well as a good setting of the establishment (Yi et al, 2018;Roy et al, 2020;Ahmed et al, 2023). The results obtained support the findings of other investigations that have proven the relationship between the CS and the CL (Yi et al, 2018;Uddin, 2019;Roy et al, 2020;Singh et al, 2021Singh et al, , 2022Purnamasari et al, 2022;Le et al, 2023) and in turn, responds to researchers who still question the influence of CS on CL and suggested that future research verify this relationship (Ahmed et al, 2023).…”
Section: Influence Of Cs On Fast-food CLsupporting
confidence: 84%
See 4 more Smart Citations
“…This finding shows that, to achieve loyalty in the fast-food customer, it is necessary that the restaurants meet the expectations of satisfaction through the delivery of quality products and services, as well as a good setting of the establishment (Yi et al, 2018;Roy et al, 2020;Ahmed et al, 2023). The results obtained support the findings of other investigations that have proven the relationship between the CS and the CL (Yi et al, 2018;Uddin, 2019;Roy et al, 2020;Singh et al, 2021Singh et al, , 2022Purnamasari et al, 2022;Le et al, 2023) and in turn, responds to researchers who still question the influence of CS on CL and suggested that future research verify this relationship (Ahmed et al, 2023).…”
Section: Influence Of Cs On Fast-food CLsupporting
confidence: 84%
“…, 2018; Uddin, 2019; Roy et al. , 2020; Singh et al ., 2021, 2022; Purnamasari et al. , 2022; Le et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations